Naked nuclei revisited: p63 immunoexpression - Reis Filho, Jorge S. (2002)
The presence of naked nuclei (NN) in cytological preparations of fibroadenomas is a well-known finding. Regardless of their importance on the differential diagnosis of fibroadenoma and other benign lesions of the breast, the origin of NN remains elusive. Despite previous efforts to characterize them, the lack of a reliable nuclear marker for myoepithelial cells impaired definitive conclusions. We performed a systematic evaluation of p63 expression in cytological and histological preparations of 10 fibroadenoma specimens. We observed that in histological sections, p63 was restricted to the nuclei of myoepithelial/basal cells in lobules and ducts of normal breast. In fibroadenomas, p63 decorated the nuclei of myoepithelial cells in the periphery of epithelial duct-like formations and slit-like formations. No p63 immunoreactivity was observed in stromal or epithelial cells. In cytological samples, almost all NN and cells surrounding epithelial cell clusters were stained; no stromal cell admixed with fibrillary matrix or epithelial cell was stained with p63. Based on our findings, we strongly suggest that most, if not all, NN are myoepithelial in origin.